E3 Ubiquitin Ligase Nedd4 Promotes Japanese Encephalitis Virus Replication by Suppressing Autophagy in Human Neuroblastoma Cells - Xu, Qingqiang (Sci Rep, 2017)
Japanese encephalitis virus (JEV) is a mosquito-borne flavivirus that causes the most prevalent viral encephalitis in Asia. Since JEV is a neurotropic virus, it is important to identify key molecules that mediate JEV infection in neuronal cells and to investigate their underlying mechanisms. In this study, the critical role of Nedd4, an E3 ubiquitin ligase that is highly expressed in the central nervous system, was examined in JEV propagation. In SK-N-SH neuroblastoma cells, Nedd4 was up-regulated in response to JEV infection. Moreover, down-regulation of Nedd4 resulted in a significant decrease in JEV replication without alterations in virus attachment and internalization or in JEV pseudotyped virus infection, suggesting that Nedd4 participates in the replication but not in the entry stage of JEV infection. Further functional analysis showed that Nedd4 attenuated JEV-induced autophagy, which negatively regulates virus replication during infection. These results suggest that Nedd4 facilitates the replication of JEV by suppressing virus-induced autophagy. Taken together, our results indicate that Nedd4 plays a crucial role in JEV infection of neuronal cells, which provides a potential target for the development of novel treatment to combat JEV infection.